2019
DOI: 10.1093/nar/gkz581
|View full text |Cite
|
Sign up to set email alerts
|

The role of ZAP and OAS3/RNAseL pathways in the attenuation of an RNA virus with elevated frequencies of CpG and UpA dinucleotides

Abstract: Zinc finger antiviral protein (ZAP) is a powerful restriction factor for viruses with elevated CpG dinucleotide frequencies. We report that ZAP similarly mediates antiviral restriction against echovirus 7 (E7) mutants with elevated frequencies of UpA dinucleotides. Attenuation of both CpG- and UpA-high viruses and replicon mutants was reversed in ZAP k/o cell lines, and restored by plasmid-derived reconstitution of expression in k/o cells. In pull-down assays, ZAP bound to viral RNA transcripts with either CpG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
165
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(177 citation statements)
references
References 82 publications
12
165
0
Order By: Relevance
“…CpGs directly or indirectly introduced into coding and noncoding regions of picornaviruses have shown that they can potently attenuate viral replication and create strains that protect animals from challenge with the wild-type virus (6-8, 10, 68). ZAP has recently been shown to be necessary for introduced CpGs to inhibit the picornavirus echovirus 7 (32). CpGs have also been shown to attenuate influenza A virus and to protect animals from lethal challenge by the wild-type virus (9).…”
Section: Discussionmentioning
confidence: 99%
“…CpGs directly or indirectly introduced into coding and noncoding regions of picornaviruses have shown that they can potently attenuate viral replication and create strains that protect animals from challenge with the wild-type virus (6-8, 10, 68). ZAP has recently been shown to be necessary for introduced CpGs to inhibit the picornavirus echovirus 7 (32). CpGs have also been shown to attenuate influenza A virus and to protect animals from lethal challenge by the wild-type virus (9).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, both ZAPS and TRIM25 inhibited HCMV virus production in an IRF3 independent manner, indicating they may play a role in directly inhibiting the virus. ZAPS and TRIM25 have recently been identified as host factors responsible for inhibiting HIV-1, Echo-7 and influenza virus constructs with synthetically increased CpG levels 9,11,20 . The two co-factors have also been reported to have antiviral activity against multiple viruses 4751 .…”
Section: Resultsmentioning
confidence: 99%
“…The fact that CpG dinucleotide patterns are so uniform across the virus sub-families also suggests a central underlying biological relevance. For example, alpha-herpesviruses are mainly associated with latent infections in neuronal cells where the interferon response may be limited due to immune privilege and constitutive expression levels of ZAP are low 20 , whereas beta-herpesviruses and gamma-herpesviruses are mainly associated with latency in haematopoietic cells and are therefore under greater pressure to evade host cell IFN responses 58 . Alternatively, alpha-herpesviruses may have evolved a robust mechanism that directly counteracts ZAP antiviral activity, making it unnecessary to repress CpG dinucleotides.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is increasingly recognised that the nucleotide composition of the genomes of viruses has a profound influence of its subsequent interaction with the cell on infection. Elevated frequencies of the CpG dinucleotide in RNA virus genomes or in mRNAs expressed during replication substantially modify replication kinetics and gene expression in mammalian viruses, including enteroviruses (1) and other RNA viruses (2)(3)(4)(5), HIV-1 (6)(7)(8) and other retroviruses (9) and hepatitis B virus (10) through their interactions with zinc finger antiviral protein (ZAP). ZAP has been shown to specifically bind to high CpG containing RNA sequences (1,8) and activate a range of RNA degradation pathways or induce translational arrest.…”
Section: Introductionmentioning
confidence: 99%